Aid, growth, and jobs - Gary Fields (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Various development objectives are worthy, but to my mind, one objective dominates all others: reducing the scourge of absolute economic misery in the world. In this paper, I focus on an important but relatively underemphasized approach to poverty reduction: helping the poor earn more in the labour market for the work they do, so that they can buy the goods and services they need to move up out of poverty.
Keywords: I3; J2; O1; O19; 330; foreign assistance; economic growth; employment; poverty; developing countries; Armut; Wirtschaftswachstum; Entwicklungshilfe; Beschäftigung; Entwicklungsländer